IMPLEMENTASI PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 34 TENTANG PENGAKUAN PENDAPATAN PADA PT BEKADA MITRATAMA BANDUNG - Endang Susilawati (LPPM POLITEKNIK LP3I BANDUNG, 2016)
ABSTRACT : Construction companies often work on projects that cross the line of the accounting period that requires the measurement and presentation of earnings right. Revenue recognition of construction service business that is a percentage of completion and completed contract method. Completed contract method recognizes all revenue and expenses at the end of the contract period of completion of the work as a whole. While the percentage of completion method recognizes revenue and cost of suit the company's progress in completing the contract and did not suspend these elements until it is resolved. The purpose of this study was to obtain an overview of the accounting of construction contracts on PT. Bekada Mitratama. This company in calculating the income of construction using completed contract method to recognize revenue on a construction project. But calculations performed by the company have not been referred to in PSAK No. 34. The completed contract method can be used to calculate the income on short-term contracts are in the process of less than one accounting period. By using the completed contract approach will provide a more reasonable so that the information presented is accurate. There are significant differences in recognizing revenues and profit of the current period using the completed contract method according to the company and by reference to PSAK No. 34.